1999
DOI: 10.1136/jnnp.66.2.207
|View full text |Cite
|
Sign up to set email alerts
|

One year outcome in mild to moderate head injury: the predictive value of acute injury characteristics related to complaints and return to work

Abstract: Objectives-To determine the prognostic value of characteristics of acute injury and duration of post-traumatic amnesia (PTA) for long term outcome in patients with mild to moderate head injury in terms of complaints and return to work. Methods-Patients with a Glasgow coma score (GCS) on admission of 9-14 were included. Post-traumatic amnesia was assessed prospectively. Follow up was performed at 1, 3, 6, and 12 months after injury. Outcome was determined by the Glasgow outcome scale (GOS) 1 year after injury a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
195
1
11

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(233 citation statements)
references
References 46 publications
11
195
1
11
Order By: Relevance
“…GCS, used as the other measure of injury severity, did not significantly differentiate those with good from those with poor outcomes. Previous studies have also reported PTA duration to be a stronger predictor of outcome than GCS (Cattelani et al, 2002;Doig et al, 2001;Fleming et al, 1999;Sherer et al, 2002;Van der Naalt et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCS, used as the other measure of injury severity, did not significantly differentiate those with good from those with poor outcomes. Previous studies have also reported PTA duration to be a stronger predictor of outcome than GCS (Cattelani et al, 2002;Doig et al, 2001;Fleming et al, 1999;Sherer et al, 2002;Van der Naalt et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This variability has led to a focus on identifying factors predicting or indicating functional outcome. Studies conducted up to 3 years after injury have found that outcome may be influenced by injury severity, as measured by Glasgow Coma Scale (GCS) scores or duration of posttraumatic amnesia (PTA), demographic factors, including age, gender, and preinjury education and employment, as well as postinjury cognitive and social factors (Brown et al, 2005;Cattelani et al, 2002;Dikmen et al, 1995b;Fleming et al, 1999;Godfrey et al, 1993;Gollaher et al, 1998;Ip et al, 1995;Levin et al, 1990;Pastorek et al, 2004;Ponsford et al, 1995;Rothweiler et al, 1998;Van der Naalt et al, 1999;Van Zomeren & Van den Burg, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the additional possibility that the deficits found in the mild TBI group may partially or completely resolve over time. Indeed, this may explain why studies often report a higher frequency of problems in the early stages after a mild TBI than in the later stages (Kibby & Long, 1996;Lishman, 1988;Van der Naalt et al, 1999). It remains to be seen whether measures designed to target the effects of diffuse damage are better able to predict which mild TBI patients will experience long-term residual problems than traditional neuropsychological tests.…”
Section: Discussionmentioning
confidence: 99%
“…Those who sustain a TBI in the mild to moderate range often experience postconcussive symptoms such as sleep disturbance, fatigue, headache pain, irritability, mood disturbances, and cognitive symptoms [9][10][11]. Cognitive symptoms in this group tend to be related to concentration, attention, processing speed, learning, memory, prospective memory, and executive functioning [10,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%